Site application of biopolymer-based soil treatment (BPST) for slope surface protection: in-situ wet-spraying method and strengthening effect verification - Seo, Seunghwan; Lee, Minhyeong; Im, Jooyoung; Kwon, Yeong Man; Chung, Moon Kyung; Cho, Gye Chun; Chang, Ilhan (Construction and Building Materials, 2021)
Recently, environmentally friendly biological soil treatment approaches have been proposed to enhance the geotechnical engineering properties of soils. Biopolymer-based soil treatment (BPST) has been verified by extensive laboratory-scale studies as an effective ground improvement method and suggested as a new reinforcing approach for levee slope owing to its soil strengthening and vegetation promotion. However, the BPST performance and governing factors in field applications have not been thoroughly understood owing to the lack of field-scale research. In this study, a BPST field application was conducted using a wet-type soil spraying method. Biopolymer binders and site soil were mixed and sprayed for slope surface protection following the general procedure of seed spraying. The in-situ application performance and effects of implementation factors such as biopolymer phase (dried powder and prehydrated solution), prior mixing time before spraying and residue mixing time during spraying, and biopolymer recipes were assessed by comparing the unconfined compressive strengths of in-situ samples collected during site spraying and uniformly mixed samples prepared in the laboratory. The solution form of the biopolymer was advantageous for a better quality (similar to the laboratory-scale performance with uniformity) when it was priorly mixed for at least 20 min at a mixing volume of 1 m3. The field-scale implementation and quality analysis of the biopolymer-based binder in this study can contribute to narrowing the gap between field and laboratory performances and qualities.
Keywords: Beta-glucans; Biopolymer-based soil treatment; Biopolymer–site soil mixing; Field application; In-situ application; Slope surfaces; Soil mixing; Soil treatments; Surface protection; Wet spraying; Beta-glucan; Biopolymer-based soil treatment; Biopolymer–site soil mixing; In-situ application; Starch; Wet spraying; Xanthan gum